Towards a calculus of state-based software components - Barbosa, L. S. (2003)
This paper introduces a calculus of state-based software components modelled as concrete coalgebras for some Set endofunctors, with specified initial conditions. The calculus is parametrized by a notion of behaviour, introduced as a strong (usually commutative) monad. The proposed component model and calculus are illustrated through the characterisation of a particular class of components, classified as separable, which includes the ones arising in the so-called model oriented approach to systems’ design.